Bioactive macro/micro porous silk fibroin/nano-sized calcium phosphate scaffolds with potential for bone-tissue-engineering applications. (March 2013) - Yan, Le-Ping; Silva-Correia, Joana; Correia, Cristina; Caridade, Sofia G; Fernandes, Emanuel M; Sousa, Rui A; Mano, João F; Oliveira, Joaquim M; Oliveira, Ana L; Reis, Rui L
Aim: The development of novel silk/nano-sized calcium phosphate (silk/nano-CaP) scaffolds with highly dispersed CaP nanoparticles in the silk fibroin (SF) matrix for bone tissue engineering.Materials & methods: Nano-CaP was incorporated in a concentrated aqueous SF solution (16 wt.%) by using an in situ synthesis method. The silk/nano-CaP scaffolds were then prepared through a combination of salt-leaching/lyophilization approaches.Results: The CaP particles presented good affinity to SF and their size was inferior to 200 nm when theoretical CaP/silk ratios were between 4 and 16 wt.%, as determined by scanning electron microscopy. The CaP particles displayed a uniform distribution in the scaffolds at both microscopic and macroscopic scales as observed by backscattered scanning electron microscopy and micro-computed tomography, respectively. The prepared scaffolds presented self-mineralization capability and no cytotoxicity confirmed by in vitro bioactivity tests and cell viability assays, respectively.Conclusion: These results indicated that the produced silk/nano-CaP scaffolds could be suitable candidates for bone-tissue-engineering applications. Original submitted 21 December 2011; Revised submitted 10 July 2012; Published online 24 December 2012